1988
DOI: 10.1042/bj2490305
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of fluorescence of tryptophan residues in proteins by replacement with 4-fluorotryptophan

Abstract: The tryptophan-auxotrophic Bacillus subtilis LC33 mutant strain utilizes either tryptophan or 4-fluorotryptophan for growth. Proteins therefore could be isolated from these cells in either tryptophan-containing or 4-fluorotryptophan-containing forms. Since 4-fluorotryptophan is non-fluorescent, tryptophan fluorescence would be suppressed in the 4-fluorotryptophan-containing proteins, facilitating the investigation of other chromophores either on the proteins or interacting with the proteins. This approach, pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
4

Year Published

1989
1989
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 14 publications
2
41
0
4
Order By: Relevance
“…As expected, the congeners show almost no fluorescence activity due to the incorporation of (4-F)Trp. 59 Right: Results of the activity assay studying the parent protein as well as the triple and quadruple congeners. The most striking observation is the correlation of the fluorine position in fluorinated Phe with the activities of the related congeners.…”
Section: Multiple Incorporation Of Different Fluorinated Amino Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, the congeners show almost no fluorescence activity due to the incorporation of (4-F)Trp. 59 Right: Results of the activity assay studying the parent protein as well as the triple and quadruple congeners. The most striking observation is the correlation of the fluorine position in fluorinated Phe with the activities of the related congeners.…”
Section: Multiple Incorporation Of Different Fluorinated Amino Acidsmentioning
confidence: 99%
“…57,58 In 1988, Bronskill and Wong demonstrated that (4-F)Trp could not only be used in 19 F NMR analysis but also facilitates the identification of the contribution of chromophores, like Tyr or Phe, to the spectroscopic features of a protein as (4-F)Trp itself is a non-fluorescent Trp analog. 59 In addition, fluorinated Trp analogs have in general been commonly used to perform spectroscopic and unfolding studies (vide infra and e.g. ref.…”
Section: Biological Incorporation Of Fluorinated Amino Acids Into Pepmentioning
confidence: 99%
“…An analogue of tryptophan, 4-fluorotryptophan, was recently shown to have no fluorescence at room temperature (Bronskill & Wong, 1988), and these authors suggested that substitution of 4-fluorotryptophan for tryptophan in proteins would result in the suppression of tryptophan fluorescence. Therefore fluorescence from an individual tryptophan residue of particular interest (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…located at the active site of an enzyme) could be seen by substituting the other tryptophan residue(s) with 4-fluorotryptophan residue(s). Another suggested use (Bronskill & Wong, 1988) of the 4-fluoro analogue was in the elimination of all of the tryptophan fluorescence, allowing tyrosine and phenylalanine fluorescence to be seen (Konev, 1967;Lakowicz, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…This difference in the effect upon the tryptophans between these 2 CaBPs may be due to the dimeric nature of CT as opposed to the monomeric nature of calmodulin, and suggests that the tryptophans may be used in the future as a sensitive probe in studies dedicated to why CT binds with higher affinity to calponin than calrnodulin does and the type of structural changes that this binding induces in calponin. The complicated tryptophan fluorescence response of C P 1-228, in which the 2 tryptophans may be experiencing opposing environments, together with the lack of tryptophan response of native calponin, may be further investigated by the replacement of the tryptophans with probes of altered fluorescent properties such as 5-hydroxytryptophan (Hogue et al, 1992), or the nonfluorescent analogue 4-fluorotryptophan (Bronskill & Wong, 1988). This would allow the response of the individual tryptophans to be examined, each one of which appears to be located in a domain of interaction with the CaBPs, and may well produce very informative results about the relative behavior of these 2 binding events.…”
Section: Discussionmentioning
confidence: 99%